2005
DOI: 10.1142/s0192415x05003004
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng and Diabetes

Abstract: Ginseng is a well-known medicinal plant used in traditional Oriental medicine. In recent decades, ginseng root has gained popularity as a dietary supplement in the United States. Ginseng has also been commonly used in Oriental medicine to treat diabetes-like conditions. The present review discusses the research on the anti-diabetic effects of ginseng and the possible mechanisms of its anti-diabetic actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 31 publications
1
93
0
1
Order By: Relevance
“…7) Because herbal medicines are extracted from raw botanical materials, control of the sources of botanical material is the first step in quality assurance of herbal medicines. 8,9) Recent developments in biological techniques, such as molecular genetic markers, allow for the identification of plant species through the detection of species-specific alleles. Compared to chemical constituents, genomic characters are stable for a certain plant species or population, and can be used as a marker for the discrimination of plant species or populations.…”
mentioning
confidence: 99%
“…7) Because herbal medicines are extracted from raw botanical materials, control of the sources of botanical material is the first step in quality assurance of herbal medicines. 8,9) Recent developments in biological techniques, such as molecular genetic markers, allow for the identification of plant species through the detection of species-specific alleles. Compared to chemical constituents, genomic characters are stable for a certain plant species or population, and can be used as a marker for the discrimination of plant species or populations.…”
mentioning
confidence: 99%
“…The use of this herb has been spread worldwide due to its therapeutic effects. Well-known biochemical and pharmacological effects include anti -aging, anti-diabetic, anti-fatigue, along with promoting the synthesis of DNA, RNA and proteins (Attele et al, 2002;Xie, Mehendale, and Yuan 2005;Christensen 2008;King and Murphy 2010). Studies have also shown that ginseng has beneficial effects on the central nervous system, cardiovascular system, and immune system (Block and Mead, 2003; Cancer prevention and inhibition of tumor growth are among other effects (Shin et al, 2000;Shibata 2001;Wang et al, 2007;King and Murphy, 2010).…”
Section: About Ginsengmentioning
confidence: 99%
“…They have shown that this extract modulates proteins involved in regulating inflammatory pathways and regulate carbohydrate metabolism in human skeletal muscle culture, respectively [73,74]. Panax ginseng has been used to treat diabetes [75]. The previous studies with plants have been performed to obtain potential biomarkers for the pathogenesis of diabetes and following studies were carried out by Cho [76,77] & Cho et al [78,79] to analyse antidiabetic actions of ginsenoside Re.…”
Section: /6mentioning
confidence: 99%